2011
DOI: 10.1074/jbc.m110.163444
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein H1/H2-dependent Unsplicing of Thymidine Phosphorylase Results in Anticancer Drug Resistance

Abstract: Thymidine phosphorylase (TP) catalyzes the conversion of thymidine to thymine and 2-deoxyribose-1-phosphate. The latter plays an important role in induction of angiogenesis. As such, many human malignancies exhibit TP overexpression that correlates with increased microvessel density, formation of aggressive tumors, and dismal prognosis. Because TP is frequently overexpressed in cancer, pro-drugs were developed that utilize TP activity for their bioactivation to cytotoxic drugs. In this respect, TP is indispens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 59 publications
0
38
0
Order By: Relevance
“…Altered ARVCF Expression Leads to Changes in Pre-mRNA Splicing-All three ARVCF-interacting proteins were reported to be involved in splicing of pre-mRNA (33,36,37). Therefore, we tested whether ARVCF also influences splicing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Altered ARVCF Expression Leads to Changes in Pre-mRNA Splicing-All three ARVCF-interacting proteins were reported to be involved in splicing of pre-mRNA (33,36,37). Therefore, we tested whether ARVCF also influences splicing.…”
Section: Resultsmentioning
confidence: 99%
“…The other genes identified were grouped into the subcategories mRNA-processing, DNA-associated, and cytoskeleton-associated (Table 1). Two independent clones corresponded to the HNRNPH2 gene that is involved in mRNA processing (33,34). Similarly, RNA helicase p68/DDX5 has been shown to contribute to mRNA processing (35,36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is seen in contrast to the inverse effect of TP expression on response to 5-FU. One putative mechanism of loss of function of TP is abnormal pre-mRNA splicing by increased levels heterogeneous nuclear RNP (hnRNP) H/F splicing factors which leads to loss of function of the TYMP gene [Stark et al 2011]. Further research is ongoing in regards to exact mechanisms of development of resistance specifically to capecitabine that may be distinct from other FPs.…”
Section: Oral Fpsmentioning
confidence: 99%
“…16,17 Moreover, hnRNP H1 has been associated with leukemia chemo-resistance via its impact on thymidine phosphorylase (TP) splicing. 18 In addition to these targeted analyses, genome-wide studies have revealed hnRNP H1s role, in conjunction with hnRNP F, in promoting both exon inclusion and skipping. 8 Other recent studies have linked hnRNP H1 to alternative cleavage and polyadenylation, 6 and established the cooperative roles of the hnRNP proteins in the regulation of splicing.…”
Section: Introductionmentioning
confidence: 99%